The Effect of Intraoperative Sounds of Saw and Hammer on Psychological Condition in Patients with Total Knee Arthroplasty: Prospective Randomized Study - Erkam Kömürcü; Hasan Ali Kiraz; Burak Kaymaz; Umut Hatay Gölge; Gürdal Nusran; Ferdi Göksel; Hasan Şahin; Dilek Ömür; Volkan Hancı (The Scientific World Journal)
Purpose. Surgical procedures are likely to be stressful for patients and their families. Total knee arthroplasty (TKA) is a major surgical procedure used in the treatment of osteoarthritis. During this procedure the sounds of the saw and hammer may irritate the patient and adversely affect mood. The present study examines the effect of these intraoperative sounds during TKA on postoperative mood and anxiety, by comparing two different anesthetic procedures. Methods. A total of 40 patients who underwent TKA for grade IV gonarthrosis participated in the study. Patients were randomly divided into two groups: 20 patients in the general anesthesia group and 20 patients in the spinal anesthesia group. Mood and anxiety changes were evaluated using the Profile of Mood States (POMS) and State-Trait Anxiety Inventory (STAI) instruments, respectively. Results. The postoperative POMS value in the spinal anesthesia group was definitively higher than the general anesthesia group, though the difference in preoperative and postoperative POMS and STAI scores between the two groups was not significant. Conclusion. It would seem that sounds of hammer and saw have no evident negative effect on patient’s mood. Regional anesthesia is advisable for TKA patients and appropriate sedation can be administered during the operation if needed.